Women empowerment through cultural and socialist ecofeminism in Kaine Agary’s yellow-yellow and Christie Watson’s tiny sunbirds far away - Elizabeth, Ikechi Chioma (2021)
Most research in the field of ecofeminism has been limited to environmental issues, focussing predominantly on the effects of environmental destruction on women. Some researchers have examined victimized women in the light of ecological-feminism with reference to realism, poverty, hardship and the concept of the sexualised body. But my research strives to focus on fictional characters who suffer double exploitation but still strive to continue life irrespective of the challenges. These characters suffer exploitation and marginalization in their own home, which could be more distressing and become a driving force of resistance and violence that could cause harm to both the environment and its inhabitants. This aspect ecofeminism in literature has rarely been explored. Using Kaine Agary’s Yellow-Yellow and Christie Watson’s Tiny Sunbirds Far Away, I intend to fill this gap in the literature. This study on the portrayal of African female personalities provides a key to understanding the special qualities of contemporary African female writings in relation to the plight of women, their representation in the environment and incentives for empowerment through examining the characters Binaebi, Zilayefa, Mama, Blessing and Grandma. This study is intended to expose the wrong notion that women are “weaker vessels” as it interprets female strength in the mist of ecological crises that directly and indirectly affect them. This study therefore employs ecofeminism as a theory that shows the relationship between the exploitation of women and the destruction of the natural environment. This is accomplished by using Carolyn Merchant’s concept of ecofeminism with reference to cultural and socialist ecofeminism in her book Radical Ecology as an analytical tool. The analysis is aimed at studying the female characters, their connection with the environment, the effects of ecological crises and the socio-economic conditions of women in the rural areas of Africa. This study also brings to light the motivation of women to gain empowerment using Konte and Tirivayi’s idea as it relates to African women in Women and Sustainable Human Development: Empowering Women in Africa (Gender, Development and Social Change). This study concludes that the exploration of the natural resources in the Niger-delta for profit making reveals that women and nature are extremely exploited. This study suggests strong environmental policies to save both the African women and the environment which will balance up their socio-economic status and personality in the society.